Can socioeconomic and psychosocial factors predict the duration of orthodontic treatment?. (3rd October 2019) - Nakhleh, Kamal; Joury, Easter; Dean, Rabia; Marcenes, Wagner; Johal, Ama
Summary: Introduction and objectives: Very little is known about the role of socioeconomic and psychosocial factors in predicting orthodontic treatment duration. Thus, this study aimed to test whether socioeconomic position (SEP) and psychosocial factors, namely, family environment and resiliency can predict orthodontic treatment duration. Methods: Data were analysed from a hospital-based, prospective, longitudinal study that recruited 145 consecutively selected 12- to 16-year-old male and female adolescents. Baseline SEP and psychosocial data were collected by a validated child self-completed questionnaire before the placement of fixed appliances. Linear regression analysis was used. Results: The response rate was 98.6 per cent and the dropout was 8.2 per cent. Maternal emotional support was an important predictor of orthodontic treatment duration. Adolescents with high levels of maternal emotional support were more likely to have a shorter orthodontic treatment duration (by nearly four months) than those with low levels of maternal emotional support ( P = 0.02). Parental SEP, paternal emotional support, maternal and paternal control, as well as resiliency were not significantly associated with orthodontic treatment duration ( P > 0.05). The multivariable regression analysis (including age, gender, and malocclusion severity) confirmed the significance of maternal emotional support as a predictor of orthodontic treatment duration. Conclusions: Maternal emotional support is an important predictor of orthodontic treatment duration. This may be explained by a higher maternal involvement in the orthodontic treatment, which may have facilitated achieving the required orthodontic treatment outcome in a shorter treatment duration.